Глибинні геоелектричні дослідження Голованівської шовної зони - Бурахович, Т.К.; Ширков, Б.І. (Геоінформатика, 2015)
Отримано нові експериментальні спостереження електромагнітного поля Землі в межах Голованівської шовної зони та зроблено їх обробку за допомогою сучасного програмного комплексу PRC_MTMV. На основі аналізу та інтерпретації даних магнітотелуричного зондування та магнітоваріаційного профілювання виявлено нові зони аномалій електропровідності в земній корі, які пов’язані з глибинними розломами та насувами Українського щита: Тальнівським, Ємилівським, Первомайським та Журавлинським. Розглянуто ймовірну природу аномалій електропровідності зазначеної зони та їх зв’язок з корисними копалинами. Получены новые экспериментальные наблюдения электромагнитного поля Земли в пределах Голованевской шовной зоны и выполнена их обработка с помощью современного программного комплекса PRC_MTMV. На основе анализа и интерпретации данных магнитотеллурического зондирования и магнитовариационного профилирования выявлены новые зоны аномалий электропроводности в земной коре, которые связаны с глубинными разломами и надвигами Украинского щита – Тальновским, Емиловским, Первомайским и Журавлинским. Рассмотрена вероятная природа аномалий электропроводности данной зоны и их связь с полезными ископаемыми. Purpose. The purpose of the paper is to perform magnetotelluric sounding and magnetovariation profiling investigations, with their further processing and interpretation; to allocate low resistivity zones and to determine their spatial, geological, tectonic, and metallogenic confines.
Design/methodology/approach. We used field experimental MTS and MVP investigations, processed these data using software system PRC_MTMV, and performed a qualitative interpretation of the results.
Findings. Scientific studies show that different region joint of tectonic plates (oceanic and continental, intercontinental) are characterized by conductive structures. The nature of such deep regional conductive anomalies are not necessarily explained by partial melting and may be the result of fluid migration and consequently ore component migration from the crust and mantle during the tectono-magmatic activation. Thus, the conductivity anomalies are among the most important factors to determine the possible area of geodynamic processes and should be examined in terms of the formation and location of mineral deposits. According to various scientists, Golovanivsk suture zone (GSZ) is a regional structure with low conductivity of the crust. It is characterized by a pronounced anisotropy of the subsurface resistivity and its sharp variability both in lateral direction and in depth. Deep fault zones (Talnivska, Pervomayska, Vradiyivska, Gvozdavska) limiting GSZ and its structural-formational parts stand out as high conductivity zones, both at the subsurface and at depths of 15-30 km. A processing of modern magnetotelluric observations using digital equipment on the “Pervomajskiy” profile using software system PRC_MTMV [3] made it possible to identify the anomalous conductive parts of GSZ localized in zones of deep faults (Talnivska, Pervomayska, Yemylivska).
Practical value/implications. Deposits of chromium and nickel, cobalt and platinoids, radioactive metals and gold in GSZ are within the confines of the deep fault zones that stand out in the form of low resistivity elongated anomalies.